Over a million students use our free study notes to help them with their homework
y = 3x4-8x3-3dy/dx = (3 x 4)x3-(8 x 3)x2 dy/dx = 12x3 - 24x2
The first step is deciding on the method of integration. For this integral it makes the most sense to use substitution.Let u = x2 + 1Differentiate w.r.t x => du/dx = 2xRearrange for dx=> ...
Integrate by parts:u = ln(x) u' = 1/x v' = 1 v = xBy parts formula: uv - ∫u'v dx Therefore we have: xln(x) - ∫x1/x dx = xln(x) - ∫1 dx = xln(x) - x (+c)
The chain rule is used to find the derivative of an expression in the form h(f(x)) where you have a function in terms of a function of x for example:h(f(x)) = 2(3x+1)^3 where f(x) = 3x+1 In or...
sin(2x)=sin(x+x) =sin(x)cos(x)+cos(x)sin(x) =2*sin(x)*cos(x); cos(2x)=cos(x+x) =cos(x)cos(x)-sin(x)sin(x) =[cos(x)]2-[sin(x)]2 Now let x+y=a and x-y=b, then x=(a+b)/2 and y=(a-b)/2. ...
←
152
153
154
155
156
→
Internet Safety
Payment Security
Cyber
Essentials